A road map for scaling up of freshwater prawn (Scampi) farming in India - Pillai, Bindu R; Panda, D (Indian Farming, 2024)
This article discusses the current status, challenges, and potential for the revival of scampi farming in India, focusing on the states of Andhra Pradesh, West Bengal, and Odisha. It highlights the decline in scampi production over the years due to various factors such as poor seed quality, disease outbreaks, and increased farming costs. However, recent initiatives, including the development of a genetically improved scampi breed and promotion of polyculture, show promise for revitalizing the industry. The article proposes an action plan to achieve a target production of 50,000 tonnes of scampi annually by promoting polyculture and establishing new hatcheries. It emphasizes the need for collaborative efforts among policymakers, research institutions, hatchery operators, and farmers to realize the potential of scampi farming in India.